(untitled) (Journal of Asian Geography, 2026)
Understanding the livelihoods of the urban poor is crucial for addressing poverty and promoting inclusive development. Women in urban slum areas face particular barriers to economic participation due to traditional gender roles and limited qualifications. Home-based work (HBW), however, enables many of these women to engage in income-generating activities within their domestic environment. Despite its importance for poor households and its contribution to the national labour force, HBW remains largely invisible within development interventions and policy frameworks in Bangladesh. This study explores the nature of women’s HBW in Dhaka city slums and assesses their livelihoods through the lens of the Sustainable Livelihoods Approach (SLA). A mixed-methods design was employed, combining questionnaire surveys of 200 women home-based workers with in-depth case studies across four slum areas. Data were analysed using both descriptive and inferential statistical techniques. The findings indicate that women possess low to moderate levels of livelihood capital and have limited institutional access. HBW is primarily survival-oriented rather than growth-oriented, and workers are generally unable to withstand shocks such as COVID-19 or economic downturns. Nevertheless, HBW outcomes, particularly its contribution to household income, are significant. Based on the behaviour of livelihood capital under stress, HBW can be considered moderately sustainable. The study concludes that, despite structural constraints, women engaged in HBW can enhance their livelihoods. With adequate support and greater institutional inclusion, HBW could evolve into a more resilient livelihood strategy and contribute to reducing urban poverty in the long term.